Removal of Paranitrophenol by Adsorption on Intercalated Natural Clay - Ouahida Khireddine; Yamina Berredjem; Ridha Djellaibi; Nadia Bensid; A.E.K. Gheid; A. Bouras (American Scientific Publishers, 2015)
The present work aims to the valorization of locally available clay for water remediation. The used raw material is a clay soil from the region of Guelma (Algeria). Several physico-chemical treatments have been realized in order to obtain purified clay. The characterization of the sample clay, performed using XRD, FT-IR, DTA and SEM, showed its morphology and its texture. Furthermore, the results correlated to the structural analysis, demonstrated that this clay is a disordered kaolinite of type 1:1. The adsorption experiments of parnitrophenol (PNP) in aqueous medium have been carried out using the raw kaolinite and the urea-intercalated kaolinite. The results showed that thecapacity of PNP adsorption on the intercalated kaolinite is more important than that of raw material, where it is 11.06 mg·g−1 and 7.90 mg·g−1 for the urea-intercalated kaolinite and the raw kaolinite respectively. The evaluated experimental values of the adsorption isotherms are in agreement with Langmuir and Freundlich models. In all cases, the adsorption kinetics follows the mechanism of pseudo-second order. In addition, the thermodynamic study indicates that the adsorption of PNP on raw kaolinite and urea-intercalated kaolinite is a spontaneous process.